1999
DOI: 10.1097/00007632-199906150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Atlas–Axis Facet Asymmetry

Abstract: Asymmetrical joint geometry is common and causes asymmetrical joint dynamics. Thus, a clinician attempting to palpate vertebral motion would be misled by assuming that perceived restricted joint motion universally represented a finding potentially amenable to manipulation. For spine palpation to be a valid indicator for manipulation, the clinician applying it must first be able to differentiate between asymmetrical motion caused by vertebral fixation and that caused by asymmetrical joint anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…It suggests that such a discrepancy in an asymptomatic individual is 'normal' and should not be assumed by therapists to be necessarily 'dysfunctional'. This is consistent with other studies that have indicated asymmetries of joint geometry and ROM in other regions, such as the atlas-axis articulation 27 and sacroiliac joint 28,29 , are commonly found in normal populations.…”
Section: Spinal and Peripheral Jointssupporting
confidence: 93%
“…It suggests that such a discrepancy in an asymptomatic individual is 'normal' and should not be assumed by therapists to be necessarily 'dysfunctional'. This is consistent with other studies that have indicated asymmetries of joint geometry and ROM in other regions, such as the atlas-axis articulation 27 and sacroiliac joint 28,29 , are commonly found in normal populations.…”
Section: Spinal and Peripheral Jointssupporting
confidence: 93%
“…Because of a longer articular path on one facet, the range of motion would be accentuated on one side as compared to the other side creating not only structural asymmetry but also functional asymmetry. 2 With the dominant role of the atlantoaxial joint being rotation, there may be a relationship between variation in the morphology of the inferior facet and interpretation of both static and motion palpation results. 2,16 Variation in the structure of the atlantoaxial joint (especially variation that impacts rotation) may have significant biomechanical impact leading to upper cervical dysfunctions such as muscle spasm (especially torticollis).…”
Section: Discussionmentioning
confidence: 99%
“…A restricted motion because of natural variation (in a joint that would normally be freely movable) may wrongly suggest an abnormal position. 2 Although there is a wealth of information regarding variability and asymmetry in the normal cervical spine, symmetry is still largely assumed for the analysis, diagnosis, and management of the vertebral malposition. This holds true for many chiropractic techniques such as Gonstead, National Upper Cervical Chiropractic Association, and Atlas Orthogonal.…”
mentioning
confidence: 99%
See 2 more Smart Citations